First case of Campylobacter rectus and Solobacterium moorei mixed bacteraemia successfully identified by MALDI TOF-MS. (September 2019) - Genderini, F.G.; Martiny, D.; Ponthieux, F.; Argudín, M.A.; Gomez Galdon, M.; Zaarour, A.; Garcia, C.; Libois, A.; Gérard, M.; Dauby, N.
Abstract: Campylobacter rectus and Solobacterium moorei are anaerobic Gram-negative and Gram-positive rods, respectively, that are occasionally members of the human oral flora. Bacteraemia has rarely been reported. We present the first case of mixed C. rectus – S. moorei bacteraemia in an individual with diabetes and human immunodeficiency virus infection. Both bacteria were successfully identified by MALDI-TOF MS.